Influence of biological product on growth, development and productivity of sweet corn - Маслиёв, С. В. (Scientific Progress & Innovations, 2015)
The results of the field researches of influencing of seed’s inoculation by biological product on growth, development and productivity of hybrids of valuable vegetable culture – sweet corn are presented. Possibility of increase of the productivity and quality of products is set due to treatment of seed by microbial preparations: «Diasofit», «KL-9», «Phosphoenterine» + «Diasofit». Data of the consumption of mineral matters and water consumption are given. Recommendation of norms of application of biological product is given. The productivity of grain of sweet corn is shown. The analysis of dynamics of rejection depending on application of preparations is done.